Assessment of Age, Gender, Mating Status, and Size on Single and Repeat Flight Capabilities of Heilipus lauri Boheman (Coleoptera: Curculionidae). Issue 2 (18th March 2022) - Hoddle, Mark S; Hoddle, Christina D; Milosavljević, Ivan; Estrada-Venegas, Edith G; Equihua-Martínez, Armando
Abstract: Heilipus lauri Boheman (Coleoptera: Curculionidae) is a specialist pest of avocado fruit and is considered an incursion risk for U.S. avocado producers. At the time work reported here was undertaken the flight capabilities of H. lauri were unknown. Consequently, proactive studies were undertaken to quantify aspects of this pest's flight capabilities to inform potential future control efforts. Flight mill studies were conducted in a quarantine laboratory to measure the dispersal capacity of H. lauri with respect to gender, mating status, and size on the single and repeat flight capabilities of weevils. Gender, mating status, and size did not significantly affect measured flight parameters. Average total distances flown and flight velocity, and mean maximum flight bout distances and durations significantly declined as weevil age increased and when weevils engaged in repeat flights. Survivorship rates were significantly reduced as the number of successive flights undertaken increased. The distribution of total average flight distances flown and total cumulative flight distances flown was platykurtic. The implications of these findings are discussed in terms of developing incursion management plans. Graphical Abstract: